ADMINISTRATIVE SKILLS IN THE 21ST CENTURY OF SCHOOL ADMINISTRATORS IN UTTARADIT SECONDARY SCHOOLS - Boonmee, Waraporn; Thammasit, Phimphaka (Journal of MCU Nakhondhat, 2020)
The purpose of this research was to analyze the factors of administrative skills in the 21st century of secondary school administrators in Uttaradit. The sample groups used in the research were 410 people that include school administrators and teachers in Uttaradit. The research instruments were the 5 rating scale questionnaire with a reliability of 0.92. The statistics used for data analysis were factors analysis. The finding of this research revealed that: administrative skills in the 21st century of the secondary school administrators in Uttaradit province consisted of 5 main factors 41 variables. The first main factor comprised 11 variables of administrative skills with an eigen value of 7.636 and a percentage of covariance was 18.625. The second factor had 11 variables of teamwork skills with the eigen value of 7.259 and the percentage of covariance was 17.704. The third factor had 9 variables of planning and development skills with the eigen value of 5.977 and the percentage of covariance was 14.579. The fourth factor had 4 variables of communication and technology skills with the eigen value of 5.437 and the percentage of covariance was 13.260. The fifth factor had 6 variables of leadership skills with the eigen value of 5.178 and the percentage of covariance was 12.62. These can explain the total covariance equals to 76.797%.